2021
DOI: 10.1007/s43151-021-00061-5
|View full text |Cite
|
Sign up to set email alerts
|

Youth Attitudes Towards Their Future: the Role of Resources, Agency and Individualism in the UK

Abstract: Young adults tend to be more optimistic about the future than older people, even during social and economic crises such as those created by the COVID pandemic. In this paper, we analyse survey data from a previous economic crisis to examine why young adults remain optimistic about their personal futures, and to consider what lessons, if any, this can help us with thinking about a post-COVID future. The data in question are drawn from a unique cross-sectional survey of young adults aged 22–29 in England, Scotla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Research shows that uncertainty about important resources such as education, employment and housing can undermine young adults’ sense of optimism thus negatively impacting on their future ( Keating & Melis, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that uncertainty about important resources such as education, employment and housing can undermine young adults’ sense of optimism thus negatively impacting on their future ( Keating & Melis, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, this study concluded that policies and programs should be prioritized to reduce the long-term effects of the current pandemic on young people. Strategies should be considered that give young people a sense of optimism that the future they desire is still achievable [45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the youths who are Integrity Club members tend to have a stronger belief in understanding the importance of upholding honesty and ethical behaviors to lead a successful life. Self-efficacy is considered the strongest predictor of optimism in youth toward success in later life [20]. The comparative analysis between the two genders showed that, in general, female youths are more likely to display values that portray ethical behaviors and are more accountable for their actions than their male counterparts.…”
Section: Responsibility Usually Accounts For What You Do and What Oth...mentioning
confidence: 99%